PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA ORGANISASI LABORATORIUM PENDIDIKAN EKONOMI MINI MARKET TANIA TAHUN 2018 - -, Reshy Revanda Sahervian -; -, Bambang Wasito Adi -; -, Sunarto - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The aims of this research are: 1) to determine the influence of organization culture toward the performance organization of economic education laboratory mini market tania in 2018 2) to determine the influence of leadership toward the performance organization of economic education laboratory mini market tania in 2018 3) the influence of work discipline toward the performance organization of economic education laboratory mini market tania in 2018 and 4) to determine the influence of organization culture, leadership and work discipline toward the performance organization of economic education laboratory mini market tania in 2018. This research is a quantitative research. The population of the research was student of 2016 economic education. The sampling technique used was Sampling Jenuh. The number of samples was 53 respondents. The data collection methods used were questionnaire and documentation. The data analysis technique used was multiple linear regression.             The result of the research shows that the equity of the multiple regression is Y Y = 7,246 + 0,247 X1 + 0,305 X2 + 0,464 X3. The regression coefficient is positive which means that the organization culture is positively toward the performance organization, leadership is positively toward the performance organization and work discipline toward the performance organization. It means that the better the organization culture, the leadership and the work discipline is, the higher the performance organization achievement will be. Based on the result of the research, it can be concluded that: (1) the cultural organization is positively and significantly influential toward the performance organization which is shown by the probability value of < 0.05 (0.000 < 0.05), (2) the leadership is positively and significantly influential toward the performance organization which is shown by the probability value of < 0.05 (0.003 < 0.05), (3) the work discipline is positively and significantly influential toward the performance organization which is shown by the probability value of < 0.05 (0.000 < 0.05) and Adjusted R square value of 0,762%. It is shown that 76,2% of the performance organization is influenced by the organization culture, the leadership and the work discipline, while the rest which is 23,8% is influenced by other factors not mentioned in this research.